Analysis of Microplastics in Water and Biofilm Matrices in Lahor Reservoirs, East Java, Indonesia - Pertiwi, Putri Rahayu; Mahmudi, Mohammad; Pramudia, Zulkisam; Kurniawan, Andi (Graduate School, Universitas Brawijaya, 2022)
One of the aquatic ecosystems that are very susceptible to contamination is the reservoir ecosystem. Reservoirs have different characteristics from other water bodies because they receive continuous water input from the river that flows through them. The river water contains organic and inorganic materials that can cause pollution caused by various kinds of human activities. The pollutant that is currently getting more attention is microplastics. Hence, various ways are developed to monitor the presence of microplastics in environments. The biotic component that may adsorb and accumulate microplastics is microbes that formed biofilm matrices as a predominant habitat. This study analyzes the presence of microplastics in water and biofilm matrices in Lahor Reservoir. The water parameters (pH, dissolved oxygen, temperature, and flow velocity) were also measured. Samplings were carried out at three stations, namely station A (inlet channel), station B (middle), and station C (outlet channel). This study revealed that water quality parameters were still relatively good according to the environment's quality standards. The average value of microplastic abundance in water at station A was 0.0013 particles.mL-1, station B was 0.00083 particles.mL-1, and station C was 0.00072 particles.mL-1. The average abundance of microplastics in the biofilm at station A, station B, and station C was 7.55 particles.g-1, 7.26 particles.g-1, and 4.59 particles.gram-1, respectively. This study indicates that the abundance of microplastics in the biofilm in the Lahor Reservoir was thousands of times higher than in the water. According to the results of this study, the biofilm can be used as a biological agent in monitoring the presence of microplastics in aquatic ecosystems such as the Lahor Reservoir, East Java, Indonesia. Keywords: Aquatic Ecosystem, Biofilm, Microbial Ecology, Microplastics, Water Pollutant.